The Internal Factors Influencing Students’ Motivation in Learning English at Grade Eleventh of Man Tolitoli - Fajri; Jaya; Ismail Yunus (Universitas Insan Budi Utomo, 2026)
The objective of this This study investigates the internal factors influencing students’ motivation in learning English at the eleventh grade of MAN Tolitoli. Using a descriptive qualitative design, data were obtained through semi-structured interviews and classroom observations involving eight students selected purposively. The findings indicate that three internal factors—self-confidence, interest, and personal goals—play significant roles in shaping students’ English learning motivation. Students with higher self-confidence participated more actively in speaking activities and class discussions, whereas those with low confidence tended to remain passive due to fear of making mistakes. Learning interest, stimulated through interactive classroom activities and exposure to English media, was found to enhance engagement. Personal goals such as aspirations for higher education and future careers also encouraged students to persist despite challenges. These internal factors collectively influence students’ willingness to participate, sustain effort, and develop positive attitudes toward learning English. The study highlights the importance of fostering confidence, strengthening interest, and supporting students’ goals to improve motivation in English learning.